1999
DOI: 10.1021/bi990861o
|View full text |Cite
|
Sign up to set email alerts
|

Toward Tailoring the Specificity of the S1 Pocket of Subtilisin B. lentus:  Chemical Modification of Mutant Enzymes as a Strategy for Removing Specificity Limitations

Abstract: In both protein chemistry studies and organic synthesis applications, it is desirable to have available a toolbox of inexpensive proteases with high selectivity and diverse substrate preferences. Toward this goal, we have generated a series of chemically modified mutant enzymes (CMMs) of subtilisin B. lentus (SBL) possessing expanded S(1) pocket specificity. Wild-type SBL shows a marked preference for substrates with large hydrophobic P(1) residues, such as the large Phe P(1) residue of the standard suc-AAPF-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Site-directed mutagenesis has been successful in redesigning the substrate specificity of a large number of common classes of enzymes, including oxidoreductases (dehydrogenases and trypanothione/glutathione reductases ), hydrolases (acetylcholinesterases, β-lactamases, and proteases ), transferases (aminotransferases and glutathione- S -transferase , ), and restriction enzymes. These experiments demonstrate that rational approaches based on a three-dimensional structure or amino acid sequence alignments can succeed at changing ligand recognition. In each of the examples that follow the chemical mechanism of the reaction remains unaltered.…”
Section: Examplesmentioning
confidence: 99%
“…Site-directed mutagenesis has been successful in redesigning the substrate specificity of a large number of common classes of enzymes, including oxidoreductases (dehydrogenases and trypanothione/glutathione reductases ), hydrolases (acetylcholinesterases, β-lactamases, and proteases ), transferases (aminotransferases and glutathione- S -transferase , ), and restriction enzymes. These experiments demonstrate that rational approaches based on a three-dimensional structure or amino acid sequence alignments can succeed at changing ligand recognition. In each of the examples that follow the chemical mechanism of the reaction remains unaltered.…”
Section: Examplesmentioning
confidence: 99%
“…The presence of up to three negative charges in the various SBL subsites resulted in up to 11-fold decreased activity using a normal SBL substrate, suc-AAPF-pNA. The mutant at position 166 was chosen for additional studies which examined the effects of anionic chemical substitutions ( 8 − 8 through 8 − 10 ) on the hydrolysis of a charge-complementary cationic substrate . The resulting constructs showed up to 9-fold improvements in k cat / K M for the substrate su-AAPR-pNA and a concomitant 61-fold improvement in suc-AAPR-pNA/suc-AAPF-pNA selectivity.…”
Section: Specificity Modificationmentioning
confidence: 99%
“…Earlier mutagenesis study of B. subtilis subtilisin E indicated that the residues of Gly-166 and Asn-218 are involved in substrate binding site, which explains their effects on catalytic activity and thermostability [6,27]. Gly-166 and Asn-218 were targeted to change the amino acid residues in AprE51.…”
Section: Resultsmentioning
confidence: 99%